2017
DOI: 10.1016/j.pt.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

EPCR and Malaria Severity: The Center of a Perfect Storm

Abstract: Severe malaria due to Plasmodium falciparum infection causes nearly half a million deaths per year. The different symptomatology and disease manifestations among patients have hampered understanding of severe malaria pathology and complicated efforts to develop targeted disease interventions. Infected erythrocyte sequestration in the microvasculature plays a critical role in the development of severe disease and there is increasing evidence that cytoadherent parasites interact with host factors to enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 118 publications
(165 reference statements)
2
75
0
Order By: Relevance
“…While most cases of clinically apparent malaria are uncomplicated and present with fever and malaise, approximately 1% are severe, with mortality rates of 6.1% in children and 35.6% in adults (Bernabeu and Smith, 2017; Dondorp et al, 2008). Cerebral malaria (CM) is of paramount importance, largely because the mortality rate is high and the pathogenesis is poorly understood.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While most cases of clinically apparent malaria are uncomplicated and present with fever and malaise, approximately 1% are severe, with mortality rates of 6.1% in children and 35.6% in adults (Bernabeu and Smith, 2017; Dondorp et al, 2008). Cerebral malaria (CM) is of paramount importance, largely because the mortality rate is high and the pathogenesis is poorly understood.…”
mentioning
confidence: 99%
“…The interaction between PfEMP1 and host cell proteins is mediated by extracellular binding domains known as Duffy binding-like (DBL) domains and/or cysteine-rich interdomain regions (CIDRs). Multiple studies have identified groups of var transcripts that are elevated in pediatric patients with severe malaria (reviewed in Bernabeu and Smith, 2017). It is essential to note that although the pathogenesis of CM remains controversial, the presence of parasite sequestration in the brain is a pathologic hallmark for the illness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While expression of EPCR-binding PfEMP1s has been associated with all forms of severe malaria [16,[38][39][40][41], probably due to broad tissue tropism, efficient sequestration and the proposed pathogenic consequences of receptor binding, it is not specially linked to the development of cerebral disease. A particular association with cerebral symptoms was found for parasites expressing PfEMP1s that combine both an EPCR-binding CIDRα1 domain and a DBLβ domain that can bind to ICAM-1, allowing simultaneous binding of infected erythrocytes to both ligands [38,42,43] (Figure 1).…”
Section: Do Anti-disease Immunogens Have a Place In Future Malaria Vamentioning
confidence: 99%
“…IFN-γ contributes to parasitemia control by priming phagocytes for clearance of parasites (13). However, excessive inflammatory responses are harmful, especially if parasites sequester in organs (7,(14)(15)(16). Normally, as infection progresses, DC produce reduced levels of pro-inflammatory cytokines, concomitantly increasing IL-10 production, which suppresses pro-inflammatory and Th1 responses (3,4).…”
Section: Introductionmentioning
confidence: 99%